Foods Promotion to Children: Understanding the Need of Responsibility in Marketing to Children - Kaur, Pavleen (Information Management and Business Review, 2011)
Children are bombarded with various forms of promotional activities by marketers of food products. It is known that children lack the necessary ability to understand that marketers direct promotions at them after a rigorous analysis of child psychology. They use simple criteria to evaluate products, get carried away by the use of cartoon characters, beautiful/irregular shapes or premiums offered to them. Therefore, relentless promotion often leads to overconsumption of nutrition poor and high density foods, leading to several health problems in children. Although parents also need to control food intake of their children or the government should intervene to check unethical practices of marketers, yet, their efforts are rendered unsuccessful if foods marketing companies themselves do not exercise self-restraint in marketing unhealthy foods to children and also market these foods ‘heavily’. The present paper discusses these issues and seeks to attract interest of academicians, marketers and policy makers in India.